2018
DOI: 10.1080/07315724.2018.1454353
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Multi-Site Trial using Short Message Service (SMS) on Infant Feeding Practices and Weight Gain in Low-Income Minorities

Abstract: There were no significant improvements in feeding practices or in weight with the intervention. The timeline of the messages in relation to the targeted behavior may have affected the effectiveness of the intervention. Earlier dissemination of messages, higher level of intensity, longer intervention, additional contacts and inclusion of other caregivers may be needed to achieve the desired effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 42 publications
1
42
0
Order By: Relevance
“…This is a secondary analysis of data collected in participants recruited for a multi-site trial using short mobile messages (SMS) to improve infant weight in low-income minorities conducted in WIC clinics in PR and HI [24,25]. A total of 202 parents/caregivers of healthy term infants aged 0–2 months old participating in the WIC program were recruited from two WIC clinics in PR (100 participants) and four WIC clinics in HI (102 participants).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a secondary analysis of data collected in participants recruited for a multi-site trial using short mobile messages (SMS) to improve infant weight in low-income minorities conducted in WIC clinics in PR and HI [24,25]. A total of 202 parents/caregivers of healthy term infants aged 0–2 months old participating in the WIC program were recruited from two WIC clinics in PR (100 participants) and four WIC clinics in HI (102 participants).…”
Section: Methodsmentioning
confidence: 99%
“…All study visits were conducted at the WIC clinics. Details of the main study are published elsewhere [24,25].…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that feeding interventions are more successful with an increase in message frequency and when coupled with home visits and caregiver training and counselling sessions (Palacios et al, 2018). Other studies have demonstrated positive effects of feeding intervention programmes when initiated earlier during pregnancy to successfully impact caregiver decisionmaking about early feeding practices (Jiang et al, 2014).…”
Section: Healthmentioning
confidence: 99%
“…Given that the RTRN addresses many of the areas of concern raised by the WGDBRW and has much to offer the BUILD, NRMN, and CEC endeavors, the RTRN and RCMI site lead investigators convened to review their collective experience as a network addressing the science of health disparities and research that provided evidence for the benefits of multi-site research, [15][16][17][18][19][20][21][22] meaningful inclusion of diverse populations in research studies, 23,24 training, [25][26][27] and coaching models to advance the careers of underrepresented early stage investigators. 28 During RTRN-convened meetings of RCMI, principal investigators and program directors agreed on the process and timeline for data collection to support research publications and dissemination.…”
Section: The Rtrn Responds: Collecting Impact Datamentioning
confidence: 99%